PEMBUATAN ETHANOL GEL SEBAGAI BAHAN BAKAR ALTERNATIF PENGGANTI BAHAN BAKAR PADAT PARAFIN DI MEDAN LATIHAN - Sukahar; Achmad Hafid; Suparja (PPM Sdirjianbang Akademi Militer, 2022)
Bioethanol is a potential alternative fuel because the source is easily renewable. However, the use of bioethanol as a fuel substitute for kerosene is still rare. This is due to the plant that produces bioethanol is limited and constrained when the distribution is easy to spill. In addition, liquid bioethanol is more at risk of spilling and exploding easily because of its volatile nature to overcome these problems, liquid bioethanol is converted into gel bioethanol. This study aims to find the effect of water and carbopol on flash point, calorific value, and viscosity of bioethanol gel produced. The control variable in this study is bioethanol 90% (weight); stirring time is 1 hour and the variable is carbopol 0,85% ; 1,05% ; 1,25% (% weight and water 7,5% ; 7,9%; 8,3% (% weight).The Data in this study will be processed using the Surface Response method to obtain the results of the influence of each variable on the bioethanol produced and optimum operating conditions.From the research obtained, flash point is influenced by the percentage of water and the percentage of carbopol; calorific value is influenced by the percentage of water, the percentage of carbopol, and the interaction of both; viscosity is influenced by carbopol. Optimum flash point value of 21 0C and optimum calorific value of 4000 cal/g obtained under operating conditions the percentage of water is 7.9% and the total percentage of carbopol 1.09%.